An Analysis of the Screenplay Elements of the Short Film “The Note” - Sari, Celni Arora (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2023)
ABSTRACT: This study aims to find out elements of the screenplay in the short film 'The Note'. The research methodology is qualitative descriptive based on the qualitative descriptive approach by Moleong (2018). The data is collected by using a literature study that finds out the other literature related to the screenplay element and documentation by downloading the script of the short film. To achieve the purpose, the stage of analysis data that the writer carried out was reading the script, and then classifying the elements based on the classification by Beck (2007) and Proofed (2019). The research finding showed that the screenplay of the film ‘The Note’ consisted of seven elements, namely scene headings, actions, characters’ names, dialogues, parentheses, shots, and transitions. However, there is one unavailable element in this screenplay, namely extensions. Keywords: Analysis, Screenplay Element, Short Film, “The Note”